2022
DOI: 10.3390/ijerph19095125
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Video Assistant Referee System Implementation on Match Physical Demands in the Spanish LaLiga

Abstract: The present study aimed to analyze the influence of the Video Assistant Referee (VAR) on match physical demands in the top Spanish professional football league. Match physical demand data from all the matches for two seasons (2017/2018 and 2018/2019) in the First Spanish Division (n = 1454) were recorded using an optical tracking system (ChyronHego®). Total distance, relative total distance covered per minute, distance covered between 14–21 km·h−1, distance covered between 21–24 km·h−1, and distance covered at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Moreover, a recent study ( 13 ) found that effective playing time should be considered when interpreting the match running performance on professional soccer players, as non-significant differences on high-speed running and sprinting distances were found between the 1st and 2nd halves in professional soccer players when the effective playing time was considered. Lastly, another study ( 36 ) showed that total distance and relative total distance significantly decreased in seasons with VAR compared to seasons without VAR in the top Spanish professional football league. Consequently, higher effective playing time may increase the physical match demands, but more research is warranted on this topic.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, a recent study ( 13 ) found that effective playing time should be considered when interpreting the match running performance on professional soccer players, as non-significant differences on high-speed running and sprinting distances were found between the 1st and 2nd halves in professional soccer players when the effective playing time was considered. Lastly, another study ( 36 ) showed that total distance and relative total distance significantly decreased in seasons with VAR compared to seasons without VAR in the top Spanish professional football league. Consequently, higher effective playing time may increase the physical match demands, but more research is warranted on this topic.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the undoubted benefits of wearables, there are well-founded concerns regarding their implementation including: (1) limited evidence quantifying the potential beneficial effects of analysing specific parameters, (2) the quality of hardware and provided data, (3) information overload, (4) data security and (5) exaggerated marketing claims [11][12][13]. These concerns will be highlighted with particular focus on the two major sporting events reviewed, and by highlighting these concerns, we suggest that wearable devices that use biological data for sport performance undergo rigorous evaluation ensuring that these devices have received a certification of veracity [1,2] or guiding reference [14] prior to acceptance of use in elite sporting competition. This quality control process would undoubtedly be highly sought after by those individuals using them for general health monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of recent technology that aims to enhance performance, athlete safety or the overall fan experience has become a vital part of elite sport. Examples include the use of video assistant referees in football [1], advanced analysis of pitcher performance on return from injury in baseball [2] and foot-worn inertial sensors providing better understanding of running economy during distance running [3]. The rapid development of these technologies in the context of elite sport means that the guardrails associated with the rules and regulations put in place to ensure safety, fair play and the integrity of competition must be updated based on science to prevent any one team or individual from gaining an unfair advantage and to maintain a level playing field.…”
Section: Introductionmentioning
confidence: 99%
“…From video assistant referees in football to advanced pitcher performance analysis in baseball and foot-worn inertial sensors for running economy in distance running, the integration of technology is becoming increasingly prevalent in elite sports [9,18,22].…”
Section: Introductionmentioning
confidence: 99%